Analysis of gamma ray spectra from neutron activation studies - Akın, H. Levent. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1984., 1984)
Neutron activation analysis coupled with Gamma Ray Spectrometry is a powerful and highlyprecise, non-destructive elemental analysis method. In this work a program package, BUCAASA, was developed for the analysis of gamma rayspectra. The first program of the package BUCAASA/FIND, using an improved version of the method of the smoothed first derivative identifies the peaks in the spectrum. The second program BuCAASA/FIT is then used for fitting a function to the peaks for the accurate determination of peak location and peak area. The function used for fitting was developed by Ciftcioglu. The third program SUCAASA/CALIBR performs energy and efficiency calibration. The constituent nuclides together with their activities are identified by the fourth program BUCAASA/NUCLIDE which is an adapted versionof SAMP080 PART 111. All of the programs are interactive and can be used for both routine and academic work. Since they are coded in standard FORTRAN 77 programming language their implementation on other computers is easy. Implementation on microcomputers requires overlaying however.
Keywords: Gamma ray spectrometry.; Nuclear activation analysis.